There s more to Super Melissa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Oswald Tarimo, Agricultural Field Officer in Lemizuna, Tanzania, says 'Thanks to Alex Adhinzin of Benin for telling me about the other benefits (than as a tea) of the Melissa or lemon balm plant (in Spore 80). It is a very interesting plant because...